Recent advances in multi-component reactions and their mechanistic insights: a triennium review - Stephy, Elza John; Gulati, Shivani; Shankaraiah, Nagula (Organic chemistry frontiers an international journal of organic chemistry, 2021)
Multi-component reactions (MCRs) are considered to be an important methodological arsenal in synthetic and medicinal chemistry. These reactions have been strategically employed in various synthetic transformations where classical methods usually involve many steps with tedious procedures. The MCR approach provides high yields, atom-/step economy, reduced reaction time, is eco-friendly, and acts as an amenable tool for the generation of a library of new chemical entities (NCEs), especially in the drug discovery process. Extensive research has led to copious developments in the field of MCRs. The developments have emerged with different synthetic approaches, including C–H activation, coupling, and cycloaddition, and eventually, such an amalgamation has enabled access to a broad spectrum of organic frameworks. The present review summarizes recent advancements in MCRs and their mechanistic insights from the last triennium (2017–2020).